Comparative Study of Pga And INAA for Analyses Of Meteorite Samples - Wee, Boon Siong; Mitsuru, Ebihara (Nuklear Malaysia, 2011)
Prompt gamma-ray analysis (PGA) and instrumental neutron activation analysis (INAA) are essential for the study of rare samples such as meteorites because of non-destructivity and relatively being free from contaminations. The objective of this research is to utilize PGA and INAA techniques for comparative study and apply them to meteorite analyses. In this study, 11 meteorite samples received from the Meteorite Working Group of NASA were analyzed. The Allende meteorite powder was included as quality control material. Results from PGA and INAA for Allende showed in good agreement with literature values, signifying the reliabilities of these two methods. Elements Al, Ca, Mg, Mn, Na and Ti were determined by both methods and their results are compared. Comparison of PGA and INAA data using linear regression analysis showed correlations coefficients r2 > 0.90 for Al, Ca, Mn and Ti, 0.85 for Mg, and 0.38 for Na. The PGA results for Na using 472 keV were less accurate due to the interference from the broad B peak. Therefore, Na results from INAA method are preferred. For other elements (Al, Ca, Mg, Mn and Ti), PGA and INAA results can be used as cross-reference for consistency. The PGA and INAA techniques have been applied to meteorite samples and results are comparable to literature values compiled from previously analyzed meteorites. In summary, both PGA and INAA methods give reasonably good agreement and are indispensable in the study of meteorites.